2013
DOI: 10.1111/ahg.12036
|View full text |Cite
|
Sign up to set email alerts
|

A Genome‐Wide Search for Type 2 Diabetes Susceptibility Genes in an Extended Arab Family

Abstract: SummaryTwenty percent of people aged 20 to 79 have type 2 diabetes (T2D) in the United Arab Emirates (UAE). Genome-wide association studies (GWAS) to identify genes for T2D have not been reported for Arab countries. We performed a discovery GWAS in an extended UAE family (N = 178; 66 diabetic; 112 healthy) genotyped on the Illumina Human 660 Quad Beadchip, with independent replication of top hits in 116 cases and 199 controls. Power to achieve genome-wide significance (commonly P = 5 × 10 −8 ) was therefore li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 86 publications
0
20
0
Order By: Relevance
“…Few that have been reported include: (i) a T2DM case-control study on Saudi Arabian population that validated only some ( WFS1, JAZF1, SLC30A8, CDKN2A/B, TCF7L2, KCNQ1, HMG20A, HNF4A and DUSP9 ) of the T2DM genes implicated in European population3; however, the study was not adjusted for population stratification. (ii) a T2DM case-control study on Lebanese population that replicated only two ( CDKAL1 and TCF7L2 ) of the genes implicated in European population4; and (iii) a study from the United Arab Emirates5 on an extended pedigree (consisting of 178 Arab individuals) that implicated association of KCTD8, COX7B2 and GABRA4 genes with T2DM for the first time; the implicated markers have not so far been replicated in any other population.…”
mentioning
confidence: 99%
“…Few that have been reported include: (i) a T2DM case-control study on Saudi Arabian population that validated only some ( WFS1, JAZF1, SLC30A8, CDKN2A/B, TCF7L2, KCNQ1, HMG20A, HNF4A and DUSP9 ) of the T2DM genes implicated in European population3; however, the study was not adjusted for population stratification. (ii) a T2DM case-control study on Lebanese population that replicated only two ( CDKAL1 and TCF7L2 ) of the genes implicated in European population4; and (iii) a study from the United Arab Emirates5 on an extended pedigree (consisting of 178 Arab individuals) that implicated association of KCTD8, COX7B2 and GABRA4 genes with T2DM for the first time; the implicated markers have not so far been replicated in any other population.…”
mentioning
confidence: 99%
“…Previous studies in China have demonstrated association between polymorphisms at GABRR1 and diabetic cataract [63]. Recently we also demonstrated that polymorphisms in both GABA-A and GABA-B receptor pathway genes are associated with T2D in an extended family from the United Arab Emirates [85]. GABA-A receptors act as inhibitory neurotransmitters in the central nervous system.…”
Section: Discussionmentioning
confidence: 88%
“…Liang et al reported that the single nucleotide polymorphism (SNPs) of the cytochromooxidase VIIb 2(COX7B2) gene was associated with familial nasopharyngeal carcinoma [33]. A study by Al et al revealed that COX7B2 is a susceptibility gene for type 2 diabetes in an extended Arab family [34]. In addition, little is known about the roles of COX7B2 in human cancers and other diseases.…”
Section: Discussionmentioning
confidence: 99%